Multimedia resources and listening comprehension among superior basic education students at a public institution in Loja, school year 2023 – 2024 - Zambrano Santorum, Wilson Joel (2024)
The main objective of the present study was to improve listening comprehension in the English language among eighth grade superior basic education students at a public institution of Loja during the school year 2023-2024 by applying multimedia resources in classroom events. The time spent in the intervention proposed for this research was 8 weeks, in which were carried out the activities previously designed. Consequently, the methodology used in this action research was a mixed method approach, by the hand of a pre-test and post-test to gather quantitative data from participants, that then was compared with the Ecuadorian national grading scale. Also, a survey technique through a questionnaire to obtain perceptions on the application of the tools used from the sample, as well as observation technique using field notes for collecting qualitative data from each intervention carried out. Thus, for data interpretation, descriptive statistics were used to present and interpret data in figures and tables. The results showed that positively, almost all of the students involved improved their listening comprehension skill, obtaining an increase of their score average between the pre and post-test they took. Similarly, students expressed enjoyment, motivation, satisfaction and increased class participation regarding the use of multimedia resources tools such as contextual images, YouTube captioned videos and Quizizz website. In addition, due to the correct application of these resources, learners improved listening comprehension subskills specifically, pre-listening, post-listening, listening for the gist, listening for detail, and listening for vocabulary after the application of multimedia resources in their classroom activities. Key words: audiovisual material, auditory understanding, educational technology, mixed method, perceptions.